Agile project management with Scrum - Schwaber, Ken (Microsoft Press, 2004)
The rules and practices for Scrum--a simple process for managing complex projects--are few, straightforward, and easy to learn. But Scrum's simplicity itself--its lack of prescription--can be disarming, and new practitioners often find themselves reverting to old project management habits and tools and yielding lesser results. In this illuminating series of case studies, Scrum co-creator and evangelist Ken Schwaber identifies the real-world lessons--the successes and failures--culled from his years of experience coaching companies in agile project management. Through them, you'll understand how to use Scrum to solve complex problems and drive better results--delivering more valuable software faster. Gain the foundation in Scrum theory--and practice--you need to: Rein in even the most complex, unwieldy projects Effectively manage unknown or changing product requirements Simplify the chain of command with self-managing development teams Receive clearer specifications--and feedback--from customers Greatly reduce project planning time and required tools Build--and release--products in 30-day cycles so clients get deliverables earlier Avoid missteps by regularly inspecting, reporting on, and fine-tuning projects Support multiple teams working on a large-scale project from many geographic locations Maximize return on investment!